Microbial communities and mineral assemblages in sediments from various habitats at the Haima Cold Seep, South China Sea - Liang, Jianzhen; Feng, Jing-Chun; Kong, Jie; Huang, Yongji; Zhang, Hui; Zhong, Song; Tang, Li; Zhang, Si (Frontiers in Marine Science, 2023)
Cold seeps create diverse habitats in the deep sea and play an important role in the global carbon cycling. Anaerobic oxidation of methane (AOM) and biogenic mineralization are essential carbon pathways of methane and carbon transformation in cold seeps, however, the effects of habitat heterogeneity on the processes are still poorly understood. In this study, we investigated the microbial communities and mineral assemblages at distinct habitats in the Haima cold seep and their relationships with environmental factors. These habitats were classified as methane seep site (MS), seep-free faunal habitat (FH), and control site (CS). Bacterial communities were significantly different among the three habitats. ANME-3 archaea, Sulfurovum bacteria, and mineralization-associated microbes (e.g., Campylobacterales) were detected in high relative abundances at ROV2. Mineralogical analysis revealed abundant calcite minerals at the seep site, indicating that authigenic carbonate minerals were formed at highly active seep. Multivariate statistical analysis demonstrated that the concentrations of SO42–, Ca2+, and Mg2+ were significantly correlated with the presence of calcite minerals and bacterial communities. These results suggested that AOM-accompanied authigenic carbonate formation is an important factor influencing the mineral assemblages in seep habitats. This finding improves our understanding of marine microbial carbon cycling.